Symmetric centers on planar cubic differential systems. (August 2020) - Dukarić, Maša; Fernandes, Wilker; Oliveira, Regilene
Abstract: The main focus of this paper is the investigation of simultaneous existence of centers in symmetric planar polynomial differential systems. There are presented necessary and sufficient conditions for the existence of a bi-center of four families of real cubic symmetric systems. Furthermore, the conditions for the isochronicity of such bi-centers are obtained.